Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis